Ultra-small photoluminescent silicon-carbide nanocrystals by atmospheric-pressure plasmas. Issue 39 (28th September 2016) - Askari, Sadegh; Ul Haq, Atta; Macias-Montero, Manuel; Levchenko, Igor; Yu, Fengjiao; Zhou, Wuzong; Ostrikov, Kostya (Ken); Maguire, Paul; Svrcek, Vladimir; Mariotti, Davide
Abstract : Optical properties of the SiC nanocrystals with very low level of surface contamination are dramatically changed as the nanocrystals size is reduced to lower than the Bohr exciton radius. Abstract : Highly size-controllable synthesis of free-standing perfectly crystalline silicon carbide nanocrystals has been achieved for the first time through a plasma-based bottom-up process. This low-cost, scalable, ligand-free atmospheric pressure technique allows fabrication of ultra-small (down to 1.5 nm) nanocrystals with very low level of surface contamination, leading to fundamental insights into optical properties of the nanocrystals. This is also confirmed by their exceptional photoluminescence emission yield enhanced by more than 5 times by reducing the nanocrystals sizes in the range of 1–5 nm, which is attributed to quantum confinement in ultra-small nanocrystals. This method is potentially scalable and readily extendable to a wide range of other classes of materials. Moreover, this ligand-free process can produce colloidal nanocrystals by direct deposition into liquid, onto biological materials or onto the substrate of choice to form nanocrystal films. Our simple but efficient approach based on non-equilibrium plasma environment is a response to the need of most efficient bottom-up processes in nanosynthesis and nanotechnology.